Interpretasi Sistem Panas Bumi Suwawa Berdasarkan Sudut Pandang Tektonik Dan Anomali Gravitasi - Adianto, Mohamad Obby; Gustama, Muhammad Agni; Ar Rouf, Ferdian Budi (Mataram University, 2026)
The Suwawa geothermal prospect is one of the areas officially designated as a Geothermal Working Area (WKP) in Gorontalo Province, Indonesia. Despite its WKP status, the Suwawa geothermal prospect has not been comprehensively studied from a regional perspective. Previous studies have not conclusively explained the geothermal heat source and the controlling tectonic framework within the Suwawa WKP. Understanding the heat source and tectonic conditions is essential for the effective development of a geothermal working area. This paper applies seismic tomography and satellite gravity methods to elucidate the characteristics of the geothermal system in the Suwawa WKP. Seismic tomography is employed to interpret large-scale tectonic correlations, while satellite gravity data are utilized to assist in identifying potential geothermal heat sources. The seismic tomography results indicate that the tectonic setting influencing the Suwawa WKP is associated with an extensional zone in Teluk Gorontalo. Meanwhile, satellite gravity anomalies suggest that the geothermal heat source in the Suwawa WKP is likely related to a basin structure. These findings imply that the geothermal system in the Suwawa WKP is associated with lithospheric thinning processes.